2021
DOI: 10.1177/08968608211065871
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiological imaging on treatment delay and hospitalisation in patients with peritoneal dialysis-related peritonitis: A secondary analysis of the PROMPT study

Abstract: Background: In peritoneal dialysis-related peritonitis (peritonitis), delayed antibiotic therapy is associated with adverse outcomes. Identifying barriers to timely treatment may improve outcomes. Aim: To determine the impact of radiological investigations on treatment delay and predictors of hospitalisation and length of stay (LOS). Methods: Retrospective review of patients with presumed peritonitis in Western Australia. Results: In 153 episodes of peritonitis, 79 (51.6%) resulted in admission with a median L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…57 Secondary analysis of this study demonstrated that radiologic investigation in the first 24 hours was associated with a doubling of odds of antibiotic treatment delay. 59 Similarly, a study in Japan showed a three-fold higher risk of PD catheter removal after a delay of antibiotic treatment by 24 hours or more from the time of recognizing cloudy effluent. 58 Finally, a third study confirmed that antibiotic administration before hospitalization was an independent predictor of peritonitis cure.…”
Section: Treatmentmentioning
confidence: 96%
“…57 Secondary analysis of this study demonstrated that radiologic investigation in the first 24 hours was associated with a doubling of odds of antibiotic treatment delay. 59 Similarly, a study in Japan showed a three-fold higher risk of PD catheter removal after a delay of antibiotic treatment by 24 hours or more from the time of recognizing cloudy effluent. 58 Finally, a third study confirmed that antibiotic administration before hospitalization was an independent predictor of peritonitis cure.…”
Section: Treatmentmentioning
confidence: 96%
“… 3 Investigations that delay antibiotics, such as waiting for the results of radiological investigations, can be deleterious to patient care. 6 …”
mentioning
confidence: 99%